Resource review: Healing environments for children who have experienced trauma: an IRISS Evidence Search and Summary Service outline. https://www.iriss.org.uk/resources/esss-outlines/healing-environ-children - Dan Johnson (Scottish Journal of Residential Child Care)
This evidence summary attempts to answer the question, 'What are some of the elements of a healing environment for children who have experienced trauma'? The question is a worthy and important one. While the environment that children live in has often been considered it has rarely been from this perspective. The summary includes evidence from a range of literature, including mental health and architecture and states that the importance of the built environment should not be underestimated.